Insights into Substituent Effects of Benzaldehyde Derivatives in a Heterogeneous Organocatalyzed Aldol Reaction. Issue 14 (12th May 2022) - Di Carmine, Graziano; Pesciaioli, Fabio; Wang, Simeng; Sinibaldi, Arianna; Giorgianni, Giuliana; Parlett, Christopher M. A.; Carlone, Armando; D'Agostino, Carmine
Abstract: Organocatalyst immobilization onto solid supports represents a promising method for enabling asymmetric organocatalysis while retaining the advantages of heterogeneous catalysts, including catalyst separation, recycling, and the use of fixed‐bed reactors. Understanding how such heterogenized catalytic systems work is fundamental to develop and tailor more efficient ones. Herein, we have elucidated the role of reactant molecular structure on surface interactions and reactivity for asymmetric aldol reactions between benzaldehyde derivatives and hydroxyacetone catalyzed by SBA‐15 immobilized L ‐proline. NMR relaxation time analysis reveals that a stronger interaction between the aldehyde and the catalyst surface reduces catalytic reactivity, which is attributed to reduced access of hydroxyacetone to the L ‐proline surface sites, hence inhibiting the formation of the enamine intermediate between hydroxyacetone and L ‐proline. The results show that surface phenomena in these systems are important considerations for reactant selection, opening up new directions to explore in this area of research. Abstract : Adsorption : Understanding factors that affect and govern heterogenous organocatalysis is undoubtedly critical to develop new and higher performing catalysts. NMR relaxation techniques provide very useful insights into adsorption effects of the aldehyde partner in an organocatalyzed aldol reaction.